Japan's trade agreements aren't "window dressing" after all. Issue 2 (4th March 2019) - Mutsvangwa, Simba; Parsons, Craig R.; Shrestha, Nagendra
ABSTRACT: We analyze eight of the 15 existing Japanese economic partnership agreements (EPAs) from 1997 to 2012. First, we construct bilateral measures of trade barriers for Japan and its partners using input-output and trade data. Next, we conduct panel regressions using those measures and find that when Japan forms an EPA, the tariff-equivalent barrier between the two countries falls approximately 2% to 3%. Contrary to conventional wisdom, this suggests that Japan's EPAs may not be merely "window dressing" after all. This has implications for larger trade agreements in the works, such as the Regional Comprehensive Economic Partnership (RCEP).